การปรับปรุงกระบวนการออกแบบโครงการก่อสร้าง : กรณีศึกษา บริษัทออกแบบภายใน - วิภาวรรณ ตันตินันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This research aims to determine initiatives to improve the design process of construction projects executed by a case interior design firm which is facing customers complaints and handover delays. The study begins with the process mapping using the BPMN technique together with the data collected through the interviews of 13 employees and observation of work. The symptoms and the root causes of the problems are determined using the 5W1H and Why- Why methods. The causes of problems ranked in order of importance include delayed decisions made by top officer, lack of personnel with construction knowledge, and unrestricted design changes demanded by customers. Applying the ECRS principle and the House of Quality technique, key improvement initiatives are developed and include the exploitation of experts in design and construction, the establishment of KPIs for performance monitoring, and the restriction on customers design changes.